Effects of central imidazolinergic and alpha2-adrenergic activation on water intake - Sugawara A.M.; Miguel T.T.; Pereira D.T.B.; Menani J.V.; De Luca Jr. L.A. (Brazilian Journal of Medical and Biological Research, 2001)
Non-adrenergic ligands that bind to imidazoline receptors (I-R), a selective ligand that binds to alpha2-adrenoceptors (alpha2-AR) and mixed ligands that bind to both receptors were tested for their action on water intake behavior of 24-h water-deprived rats. All drugs were injected into the third cerebral ventricle. Except for agmatine (80 nmol), mixed ligands binding to I-R/alpha2-AR such as guanabenz (40 nmol) and UK 14304 (20 nmol) inhibited water intake by 65% and up to 95%, respectively. The selective non-imidazoline alpha2-AR agonist, alpha-methylnoradrenaline, produced inhibition of water intake similar to that obtained with guanabenz, but at higher doses (80 nmol). The non-adrenergic I-R ligands histamine (160 nmol, mixed histaminergic and imidazoline ligand) and imidazole-4-acetic acid (80 nmol, imidazoline ligand) did not alter water intake. The results show that selective, non-imidazoline alpha2-AR activation suppresses water intake, and suggest that the action on imidazoline sites by non-adrenergic ligands is not sufficient to inhibit water intake.